Antibacterial Efficacy of Leaf Extract Obtained from Ficus lingua Warb. ex De Wild. & T.Durand (Moraceae) Against Aeromonas Spp. Strains - Pękala-Safińska, Agnieszka; Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Kasiyan, Olha; Honcharenko, Vitaliy; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Although many species within the genus Ficus L. have been encompassed by pharmacological investigations in previous years, there are many species that have not been studied and whose ethnobotanical relevance is yet to be investigated. With this background, an attempt was made to study the in vitro antimicrobial activity of the ethanolic extracts of various plants belonging to the genus Ficus against fish pathogens. This is especially important in view of the increasing resistance of bacteria observed during the last years and is an alternative to antibiotic therapy. Therefore, the aim of this study was to screen the antimicrobial activity of the ethanolic extract of Ficus lingua Warb. ex De Wild. & T.Durand leaf against fish pathogen – three Aeromonas strains (Aeromonas sobria, Aeromonas hydrophila, Aeromonas salmonicida subsp. salmonicida). The focus of this paper is on the analytical methodologies, which include the extraction of active compounds and antimicrobial activity assay by the disk diffusion technique. It was revealed that the leaf extract of F. lingua used in this study has bactericidal properties which make it very attractive for use in fish aquaculture. Its uses will reduce the side effects of applying synthetic compounds. The ethanolic extract obtained from leaves of F. lingua exhibited the maximum antimicrobial activity against Aeromonas sobria strain (inhibition zone diameter was 19.38 ±1.27 mm), Aeromonas hydrophila (16.06 ±1.05 mm), and Aeromonas salmonicida subsp. salmonicida (11.25 ±1.16 mm). The most susceptible strain to the antimicrobial activity of F. lingua was Aeromonas sobria. However, further study is needed to determine the effects of the active compounds presented in the leaf extract of F. lingua on fish metabolism in in vitro and in vivo study. Present results suggest the possibility of using such extracts in in vivo studies in order to corroborate if it could be possible using those extracts in aquaculture in order to achieve protection against pathogenic infections.